2018
DOI: 10.3390/educsci8040165
|View full text |Cite
|
Sign up to set email alerts
|

Academic Vocabulary and Reading Fluency: Unlikely Bedfellows in the Quest for Textual Meaning

Abstract: Academic vocabulary is the specialized language used to communicate within academic settings. The Coxhead (2000) taxonomy is one such list that identifies 570 headwords representing academic vocabulary. Researchers have hypothesized that students possessing greater fluent reading skills are more likely to benefit from exposure to vocabulary due to greater amounts of time spent reading (Nagy and Stahl, 2007; Stanovich, 1986). In this study of 138 sixth- and seventh-grade students, we assess academic vocabulary,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
2
2
0
Order By: Relevance
“…As for the reading skill, in particular, some participants responded that knowledge of the AWL helped them to read academic materials (e.g., textbooks, journal articles, and other online resources) more effectively with a better understanding. The finding was in line with the previous studies that underscored the significance of word knowledge in reading comprehension skills (e.g., Laufer & Ravenhorst-Kalovski, 2010;Paige & Smith, 2018). However, some expressed concern commenting that knowledge of AWL alone would not be enough to be able to meet the targeted standard and that the language learners should learn more words than just Coxhead's AWL, particularly for English proficiency tests such as TOEIC, TOEFL, and IELTS.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…As for the reading skill, in particular, some participants responded that knowledge of the AWL helped them to read academic materials (e.g., textbooks, journal articles, and other online resources) more effectively with a better understanding. The finding was in line with the previous studies that underscored the significance of word knowledge in reading comprehension skills (e.g., Laufer & Ravenhorst-Kalovski, 2010;Paige & Smith, 2018). However, some expressed concern commenting that knowledge of AWL alone would not be enough to be able to meet the targeted standard and that the language learners should learn more words than just Coxhead's AWL, particularly for English proficiency tests such as TOEIC, TOEFL, and IELTS.…”
Section: Discussionsupporting
confidence: 88%
“…In line with the findings of Choo et al (2017), who conducted a similar study in an ESL context, this study also found EFL students held positive attitudes toward the significance of Coxhead's AWL knowledge for their academic communicative skills. These two findings affirm that Coxhead's AWL is extremely significant for university students in both ESL and EFL contexts (Srikrai et al, 2016) Paige & Smith, 2018;Staehr, 2008). By considering the evidence, this study suggests a need for a strategic approach to teaching and creating awareness of Coxhead's AWL among teachers and university students, in both ESL and EFL contexts.…”
Section: Implications and Future Researchsupporting
confidence: 73%
See 1 more Smart Citation
“…Once, the reader lucks of vocabulary, they will have the difficulties to understanding the text. Ibrahim, Sarudin, & Muhamad, (2016); Paige & Smith, (2018) mention that vocabulary knowledge is crucial component in reading comprehension. Thus, Vocabulary is one of the component materials in English subject.…”
Section: Introductionmentioning
confidence: 99%